Robotic Rehabilitation and Spinal Cord Injury: a Narrative Review - Mekki, Marwa (Neurotherapeutics, 2018)
Mobility after spinal cord injury (SCI) is among the top goals of recovery and improvement in quality of life. Those with tetraplegia rank hand function as the most important area of recovery in their lives, and those with paraplegia, walking. Without hand function, emphasis in rehabilitation is placed on accessing one’s environment through technology. However, there is still much reliance on caretakers for many activities of daily living. For those with paraplegia, if incomplete, orthoses exist to augment walking function, but they require a significant amount of baseline strength and significant energy expenditure to use. Options for those with motor complete paraplegia have traditionally been limited to the wheelchair. While wheelchairs provide a modified level of independence, wheelchair users continue to face difficulties in access and mobility. In the past decade, research in SCI rehabilitation has expanded to include external motorized or robotic devices that initiate or augment movement. These robotic devices are used with 2 goals: to enhance recovery through repetitive, functional movement and increased neural plasticity and to act as a mobility aid beyond orthoses and wheelchairs. In addition, lower extremity exoskeletons have been shown to provide benefits to the secondary medical conditions after SCI such as pain, spasticity, decreased bone density, and neurogenic bowel. In this review, we discuss advances in robot-guided rehabilitation after SCI for the upper and lower extremities, as well as potential adjuncts to robotics. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13311-018-0642-3) contains supplementary material, which is available to authorized users.